GIANT LEIOMYOSARCOMA OF THE STOMACH SHOWING A PEDUNCULATED AND CYSTIC DEVELOPMENT - SHIOYA, Keiichi; ISHIDA, Tsunehiro; MORISHITA, Yasuo; OKABE, Toshio; OHWADA, Susumu; KUSABA, Teruo (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1999)
A 45-year-old man with giant leiomyosarcoma of the stomach, which showed a pedunculated and cystic development, was successfully treated by surgical operation. The patient complaining of right hypochondralgia was referred to the hospital because of a cystic tumor adjacent to the liver. An extraluminal submucosal tumor, especially leiomyosarcoma, was preoperatively suspected. A total gastrectomy combined with splenectomy and lymph node dissection was performed. In the resected specimen, the tumor growing outside the fornix of the stomach with a large cystic change was present. It was 18×12×10cm in size and 800g in weight and involved darkred fluid (150ml). Histologically, smooth muscle actin staining was positive. The final diagnosis was leiomyosarcoma of the stomach. Giant leiomyosarcoma of the stomach showing a pedunculated development with the maximum diameter of more than 15cm is rare, and only 10 cases including this case have been reported in the Japanese literature.